Selection of Seismic Acceleration for Non-linear Analysis Of Rc Buildings in Bangladesh (Journal of Engineering Science, 2023)
Seismic acceleration selection is a vital issue of non-linear time history analysis for reinforced concrete (RC) buildings. The propagation characteristic of selected seismic acceleration through soil medium depends on the material properties of the soil and reflected waves from the structure are absorbed by the adjacent soil medium. Stiffnesses of structural members are degraded by exciting and internal waves because of storing the hysteretic strain energy inside structural members. However, this study proposes a finite element model for the selection of seismic acceleration considering specific site classes in Bangladesh based on the soil stratum because seismic excitation varies with the site class. In addition, the structural response depends on the selected acceleration, and non-linear time history analysis represents the more reliable inelastic response of the structure due to this acceleration. Variation of seismic storey drift within allowable limit indicates appropriate selection of the seismic acceleration by the non-linear response history analysis. Also, lower rates of output acceleration intensities for upper stories may inform the majority of reflected waves absorbed by the soil medium. For this reason, proper selection of seismic acceleration may enhance the accurate non-linear response of RC buildings in Bangladesh.Journal of Engineering Science 14(1), 2023, 95-109